2014 Update of the Pacific Northwest Portion of the U.S. National Seismic Hazard Maps. (December 2015) - Frankel, Arthur; Chen, Rui; Petersen, Mark; Moschetti, Morgan; Sherrod, Brian
Several aspects of the earthquake characterization were changed for the Pacific Northwest portion of the 2014 update of the national seismic hazard maps, reflecting recent scientific findings. New logic trees were developed for the recurrence parameters of M8-9 earthquakes on the Cascadia subduction zone (CSZ) and for the eastern edge of their rupture zones. These logic trees reflect recent findings of additional M8 CSZ earthquakes using offshore deposits of turbidity flows and onshore tsunami deposits and subsidence. These M8 earthquakes each rupture a portion of the CSZ and occur in the time periods between M9 earthquakes that have an average recurrence interval of about 500 years. The maximum magnitude was increased for deep intraslab earthquakes. An areal source zone to account for the possibility of deep earthquakes under western Oregon was expanded. The western portion of the Tacoma fault was added to the hazard maps.